2004
DOI: 10.5194/angeo-22-2861-2004
|View full text |Cite
|
Sign up to set email alerts
|

High-latitude poynting flux from combined Iridium and SuperDARN data

Abstract: Abstract. Field-aligned currents convey stress between the magnetosphere and ionosphere, and the associated low altitude magnetic and electric fields reflect the flow of electromagnetic energy to the polar ionosphere. We introduce a new technique to measure the global distribution of high latitude Poynting flux, S || , by combining electric field estimates from the Super Dual Auroral Radar Network (Super-DARN) with magnetic perturbations derived using magnetometer data from the Iridium satellite constellation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 47 publications
(84 reference statements)
0
44
0
Order By: Relevance
“…For example, Waters et al (2004) showed that measurements of ionospheric convection can be combined with magnetic perturbations measured by low-altitude satellites to determine the global magnetic poynting flux at high magnetic latitudes. Their technique used magnetic perturbations measured onboard the Iridium satellites, as well as ionospheric convection electric fields measured by SuperDARN.…”
Section: New Analysis Techniques/capabilitiesmentioning
confidence: 99%
“…For example, Waters et al (2004) showed that measurements of ionospheric convection can be combined with magnetic perturbations measured by low-altitude satellites to determine the global magnetic poynting flux at high magnetic latitudes. Their technique used magnetic perturbations measured onboard the Iridium satellites, as well as ionospheric convection electric fields measured by SuperDARN.…”
Section: New Analysis Techniques/capabilitiesmentioning
confidence: 99%
“…In other cases we have used SuperDARN to estimate the electric field (Waters et al, 2004), but as stated above in this event the radar returns are too sparse for this analysis. Instead, we take here advantage of excellent data from the DMSP drift meter and magnetometer instruments, favorable DMSP tracks through the regions of Birkeland currents and auroral emissions, and the sunlit ionospheric conditions (northern summer) that favor a solar EUV dominated ionospheric conductivity.…”
Section: Electromagnetic Energy Flux Estimationmentioning
confidence: 99%
“…The b-distribution is used here in the estimation of the Poynting vector. Due to the coarse time sampling of the Iridium engineering magnetometer data, on average about 200 s between samples on an individual satellite, roughly one hour of data is required to obtain a latitude resolution of approximately 4 • in the Iridium fit results (Anderson et al, 2000;Korth et al, 2004;Waters et al, 2004).…”
Section: Iridium Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, single satellites give information only along the satellite track and cannot "image" the EM input to yield the distribution of incident power. Global distributions of the largescale parallel Poynting vector, providing a complementary perspective to in-situ observations, have recently been evaluated from measurements of the magnetic perturbations at the ionosphere by the constellation of Iridium satellites and observations of the ionospheric electric field by the Super Dual Auroral Radar Network (SuperDARN) (Waters et al, 2004).…”
Section: Introductionmentioning
confidence: 99%